Towards an intersectional model of desistance for black offenders. Issue 1 (11th January 2016) - Glynn, Martin
Abstract : Purpose: – Desistance is increasingly conceptualised as a theoretical construct which is used to explain how offenders orient themselves away from committing crimes. Previous studies suggest that successful desistance occurs due to one or a number of factors. These factors include things such as: faith (Giordano et al., 2007); a rite of passage (Maruna, 2010); gender (Giordano et al., 2002); psychosocial processes (Healey, 2010); personal and social circumstances which are space and place specific (Flynn, 2010); ethnicity and faith (Calverley, 2013); race and racialisation (Glynn, 2014). However, to date there has been little work undertaken to examine how notions of "intersectionality" may be a more appropriate theoretical lens through which to locate and contextualise the understandings of desistance when looking at marginalised populations such as black offenders. Intersectionality is an understanding of human beings as shaped by the interaction of different social locations. These interactions occur within a context of connected systems and structure of power. Through such processes independent forms of privilege and oppression are created. The paper aims to discuss these issues. Design/methodology/approach: – The paper concludes with a perspective that envisions moving towards an "intersectional model of desistance for marginalised groups such as black offenders". Findings: – It is the author's view that the development of a intersectional model of desistance for black offenders may begin a dialogue that further pushes the study of re-entry and desistance into an area that transcends the criminal justice system and locates itself firmly within the civil and human rights of black offenders, and indeed, offenders as a whole. It is hoped that by using intersectional approaches when conducting inquiries we will be able to lead towards eradicating multiple oppressions faced by so many sections of the offender populations and the communities they come from. Research limitations/implications: – This paper is positional inasmuch as it attempts to establish some, principled arguments to advance the study of desistance. Therefore, a testing of the views expressed in the paper is required. Practical implications: – It is the author's contention that for those black offenders who desire to quit crime, there needs to be networks and activities that not only support their desire to desist, but a radical reframing of how interlocking oppressions that render them subordinate must become a key driver for the desistance project. How can/do black offenders acquire and tell their own authentic narrative when it has been shaped by a history of oppression? It is therefore right to assume that meaningful reintegration of black offenders back into communities requires a deeper commitment to culturally competent rehabilitative processes, that could lead towards a culture of desistance. Social implications: – An "Intersectional Model of Desistance" also needs to challenge some white criminologists' claims by validating the black contribution to criminological theorising. This position should embrace and include perspectives which unify theoretical positions that validate interlocking oppressions; racism, poverty, ethno-cultural group membership, etc., where the broader distribution of opportunities across society, and the ability to recognise them as such as opportunities for black men to desist are taken into consideration. As part of a process of rehabilitation, black offenders need to be engaged with intersectional institutional processes and practices that will lead to a challenge of their criminal values and behaviour, designed to increase their capacity to consider desistance. It is hoped that by using intersectional approaches when conducting inquiries we will be able to eradicate multiple oppressions faced by so many sections of the offender populations and the communities they come from. Originality/value: – Understanding how the experiences of black offenders, are impacted by examining interlocking oppressions of criminal justice processes; police, courts, incarceration, probation, etc., would critically assess how these intersections enhances or impedes the desistance trajectories of black offenders, in relation to offenders as a whole. As much of black offender lived reality centres on having to contend, not just with criminal justice process, but the additional oppression of racialisation, the outcomes become more heavily context dependent and driven.